(untitled) (Revista Apotheke, 2022)
The writing of this article was developed from reflections that I weave by intertwining experiences as a teacher in two different institutions: as an elementary school teacher in a municipal school in Florianópolis/SC and, as a teacher in the Visual Arts degree at UDESC/ SC. In dialogue with contributions from Visual Culture and Everyday Studies, I aim to make arguments about aspects that seem necessary to be problematized, revisited, promoted in the teacher training course, seeking to think about ways of teaching that are built more attentive to what is being present in everyday school life. And, with that, expand learning networks that are more meaningful to the actors involved in the educational process.